The Effect of Interpersonal Communication, Self Engagement and Organizational Commitment toward The Employee Performance - Abdul Ghofar; Ma'ruf Akbar; Muchlis Luddin (IJHCM (International Journal of Human Capital Management), 2018)
The objective of this reseach was to understand comprehensively the effect of Interpersonal Communication, Self-Engagement and Organizational Commitment toward the Employee Performance. It was a quantitative research with survey method in the communication and information ministery in Jakarta 2016. The data were colected through observation. The data analysis and interpretasion indicates that (1) the effect Interpersonal Communication toward the Employee Performance; (2) the effect Self-Engagement toward the Employee Performance; (3) the effect Organizational Commitment toward the Employee Performance; (4) the effect Interpersonal Communication toward the Employee Organizational Commitment; (5) the effect Self-Engagement toward the Employee Organizational Commitment; (5) the effect Interpersonal Communication toward the Employee Self-Engagement. The findings lead to the recomendation to practice effectively Employee Performance, Organizational Commitment and Self-Engagement, with Interpersonal Communication. Interpersonal Communication practice by (1) communication opens, (2) empaty, (3) supporting, (4) positif thingking and (5) equality.